Tilapia aquaculture systems in Egypt: Characteristics, sustainability outcomes and entry points for sustainable aquatic food systems - Rossignoli, Cristiano; Manyise, Timothy; Shikuku, Kelvin; Nasr-Allah, Ahmed; Brako Dompreh, Eric; Henriksson, Patrik; Dam Lam, Rodolfo; Lozano, Denise; Tran, Nhuong; Roem, Arjen; Badr, Alaa; Sbaay, Ashraf; et al. (Elsevier Ltd., 2023)
The future demand for fish and other aquatic foods requires the sustainable intensification of related production systems. However, policy and investment decisions for the sustainable intensification of aquaculture systems are usually hindered by the lack of benchmarking data about their actual sustainability performance, often resulting in poorly developed and implemented interventions that ignore potential sustainability trade-offs. This is a reality in many of the leading aquaculture producers in the developing world like Egypt. In this study we analyzed farm-level data from 402 aquaculture producers in the Kafr El Sheikh governorate in Egypt, to characterize and benchmark the performance of tilapia production systems against key sustainability outcomes. For the analysis we used a combination of statistical tools such as ordinary least square regressions, simultaneous quantile regressions and propensity score matching. We focussed on how the production characteristics and practices of different tilapia production systems intersect with economic, food security, and environmental outcomes that cover multiple dimensions of sustainability. We found that differences in these production characteristics and practices were significantly associated with the sustainability performance of tilapia production systems. In particular, our results show that yields in monocultural systems (10,460.5 ton/ha) were significantly higher than in polyculture systems (8404.7 ton/ha). Furthermore, despite the generally positive economic, food security, and environmental outcomes of several of the studied systems, some trade-offs emerge both between and within these sustainability dimensions.